Presenting a Mission-Oriented University Model and Its Impact on the Development of Sustainable Higher Education in Universities of Mazandaran Province - Fakhri, Sakineh; Salehi, Mohammad; Enayati, Taraneh (Assessment and Practice in Educational Sciences, 2025)
Mission-oriented universities conduct a precise analysis of societal needs and design their educational and research programs based on these needs. Therefore, the primary objective of the present study was to present a model of the impact of mission-oriented universities on the development of sustainable higher education in universities of Mazandaran Province. In terms of purpose, this study was applied research and employed a descriptive-survey method. The statistical population consisted of 5,878 faculty members of universities in Mazandaran Province, from whom 361 participants were selected as the sample based on Cochran’s formula using stratified random sampling. Data were collected using a researcher-made Mission-Oriented University Questionnaire containing 45 items and the Sustainable Higher Education Development Questionnaire developed by Arab (2023) consisting of 25 items. The face and content validity of the instruments were confirmed. Structural equation modeling was used for data analysis. The findings indicated that the impact of mission-oriented universities on the development of sustainable higher education in universities of Mazandaran Province was positive and significant, and the proposed model demonstrated an appropriate fit. Considering the impact of mission-oriented universities on the development of sustainable higher education, university managers and policymakers should direct universities toward mission orientation through scientific and coherent planning in order to facilitate the development of sustainable higher education within universities.